Về hiệu chỉnh bất đẳng thức biến phân trong không gian LP(W) - Buong, Nguyen (Journal of Computer Science and Cybernetics, 2018)
The new approach in the theory of regulization for variational inequality with monotone operator in Banach space is presented in LP(W) by using a linear and strongly monotone operator in place of duality mapping.